INVESTIGATION OF THE EFEECT OF TBLT-BASED DIGITAL STORYBOOK ON STUDENTS’ READING SKILL IN SMP NEGERI 6 SINGARAJA - Setiawati, I Gusti Ayu Indah; Paramartha, A.A. Gede Yudha; Wahyuni, Luh Gede Eka (Universitas Suryakancana, 2024)
The purpose of this study is to look at the major impact that TBLT-based digital storybooks have on the reading abilities of ninth-grade students at SMP Negeri 6 Singaraja. This study employed a quasi-experimental methodology and was quantitative in nature. Two classes were assigned to this study: a control class with 31 students and an experimental class with 33 students. The two classrooms received different treatments: the Experimental class used a digital storybook based on TBLT, while the Control class used the teacher's regular approach. The reading score was calculated using a reading test. The data was analyzed using the t-test formula. The outcome demonstrated that the TBLT-based digital storybook had a significant effect on the reading proficiency of the students. The Sig. (2-tailed) value of 0.036 demonstrated this. As a result, the tests' significance value was less than 0.05. This demonstrates that, as compared to students taught using the teacher's regular method, there is a significant influence on the reading skills of students who are taught using TBLT-based digital storybooks. Furthermore, 0.537 was the effect size value as determined by Cohen's d. This significant impact indicates that, in comparison to the teacher's typical approach, the use of TBLT-based digital storybooks can have a very tangible impact on students' reading skill development.